TRENDS OF DEVELOPING ECONOMIC RELATIONS OF COMMERCIAL BANKS AND BUSINESS SECTOR IN CONTEXT OF DIGITAL ECONOMY - Elena Igorevna Generalnitskaia (Science and Innovation Center Publishing House, 2019)
Background: the article describes the prospects of the digitalization of the domestic economy on the annual growth of domestic GDP, substantiates the importance of studying economic relations between credit organizations and organizations of the business sector in the context of the transition to the digital economy as economic entities that can make a significant contribution to increasing GDP.